Intrinsic motivation, external reward, and their effect on overall motivation and performance. Issue 4 (7th August 2016) - Hendijani, Rosa; Bischak, Diane P.; Arvai, Joseph; Dugar, Subhasish
ABSTRACT: An unresolved debate lingers concerning the effect of performance-contingent rewards on motivation and performance. Behavioral psychology and economics suggest that performance-contingent rewards improve performance. In contrast, cognitive evaluation theory predicts that performance-contingent rewards undermine motivation and performance. We discuss the predictions of these two streams and develop an experiment that resolves the limitations of previous studies by using a new measure of intrinsic motivation: self-selection into a specific area of knowledge, as revealed by choice of academic major. Students from mathematics-related and literature-related areas were selected and randomly assigned to math and English language tests. Participants received a participation fee or a performance-contingent payment in addition to a fee. Both performance-contingent rewards and intrinsic motivation improved motivation and performance, in contrast with cognitive evaluation theory's predictions.